Novel pathogenic variant in MED12 causing non-syndromic dilated cardiomyopathy - Serwa Ghasemi; Mohammad Mahdavi; Majid Maleki; Iman Salahshourifar; Samira Kalayinia (BMC, 2023)
Abstract Background Dilated cardiomyopathy (DCM) is a major cause of sudden cardiac death and heart failure. Up to 50% of all DCM cases have a genetic background, with variants in over 250 genes reported in association with DCM. Whole-exome sequencing (WES) is a powerful tool to identify variants underlying genetic cardiomyopathies. Via WES, we sought to identify DCM causes in a family with 2 affected patients. Methods WES was performed on the affected members of an Iranian family to identify the genetic etiology of DCM. The candidate variant was segregated via polymerase chain reaction and Sanger sequencing. Computational modeling and protein-protein docking were performed to survey the impact of the variant on the structure and function of the protein. Results A novel single-nucleotide substitution (G > A) in exon 9 of MED12, c.1249G > A: p.Val417Ile, NM_005120.3, was identified. The c.1249G > A variant was validated in the family. Bioinformatic analysis and computational modeling confirmed that c.1249G > A was the pathogenic variant responsible for the DCM phenotype. Conclusion We detected a novel DCM-causing variant in MED12 using WES. The variant in MED12 may decrease binding to cyclin-dependent kinase 8 (CDK8), affect its activation, and cause alterations in calcium-handling gene expression in the heart, leading to DCM.